Digitalisasi Sebagai Strategi Penguatan Lembaga Keuangan Mikro Syariah Di Indonesia - Haniah Lubis; Irsya Putri Awana; Naila Nazwa Lubis; Farhan Kurnia (Sharing: Journal of Islamic Economics Management and Business, 2026)
Digitalization has become an important strategy in strengthening Islamic Microfinance Institutions (LKMS) in Indonesia. This study aims to determine the role of digitalization in improving service quality and Islamic financial inclusion. The research uses a qualitative approach with a literature study method through various scientific journals, books, and articles. The results show that digitalization is able to improve service efficiency, expand public access to financial services, and support the development of MSMEs through technology-based services such as Islamic fintech and digital payments. However, its implementation still faces challenges, including low digital literacy, limited infrastructure, and the quality of human resources. Therefore, strengthening human resources, service innovation, and regulatory support are needed so that the digital transformation of LKMS can run optimally and sustainably.